Preliminary effects and acceptability of a co-produced physical activity referral intervention. (December 2019) - Buckley, Benjamin JR; Thijssen, Dick HJ; Murphy, Rebecca C; Graves, Lee EF; Whyte, Greg; Gillison, Fiona; Crone, Diane; Wilson, Philip M; Hindley, Daniel; Watson, Paula M
Objectives: To explore the preliminary effects and acceptability of a co-produced physical activity referral intervention. Study Design: Longitudinal design with data collected at baseline and post a 12-week physical activity referral intervention. Setting: Community leisure centre. Methods: In all, 32 adults with controlled lifestyle-related health conditions took part in a physical activity referral intervention (co-produced by a multidisciplinary stakeholder group) comprising 12 weeks subsidised fitness centre access plus four behaviour change consultations. A complete case analysis ( t -tests and magnitude-based inferences) was conducted to assess baseline-to-12-week change in physical activity, cardiometabolic, and psychological measures. Semi-structured interviews were conducted ( n = 12) to explore experiences of the intervention. Results: Mean improvements were observed in cardiorespiratory fitness (3.6 mL kg -1 min -1 [95% confidence interval: 1.9–5.4], p < .001) and moderate-to-vigorous physical activity (12.6 minutes per day [95% confidence interval: 4.3–29.6], p = .013). Participants were positive about the support received from exercise referral practitioners, but experienced some challenges in a busy and under staffed gym environment. Conclusions: A co-produced physical activity referral intervention elicited short-term improvements in physical activity and cardiometabolic health. Further refinements may be required, via ongoing feedback between stakeholders, researchers and service users, to achieve the intended holistic physical activity focus of the intervention, prior to a definitive trial.